Overweight, obesity and fat distribution in 50- to 64-year-old participants in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Haftenberger, M; Lahmann, P; Panico, S; Gonzalez, C; Seidell, J; Boeing, H; Giurdanella, M; Krogh, V; Bueno-De-Mesquita, H; Peeters, P; Skeie, G; Hjartåker, A; et al. (2002)
Objective: To describe anthropometric characteristics of participants of the European Prospective Investigation into Cancer and Nutrition (EPIC). Design: A cross-sectional analysis of baseline data of a European prospective cohort study. Subjects: This analysis includes study populations from 25 centres in nine European countries. The British populations comprised both a population-based and a 'health-conscious' group. The analysis was restricted to 83 178 men and 163 851 women aged 50-64 years, this group being represented in all centres. Methods: Anthropometric examinations were undertaken by trained observers using standardised methods and included measurements of weight, height, and waist and hip circumferences. In the 'health-conscious' group (UK), anthropometric measures were predicted from self-reports. Results: Except in the 'health-conscious' group (UK) and in the French centres, mean body mass index (BMI) exceeded 25.0 kg m-2. The prevalence of obesity (BMI ≥ 30 kg m-2) varied from 8% to 40% in men, and from 5% to 53% in women, with high prevalences (>25%) in the centres from Spain, Greece, Ragusa and Naples (Italy) and the lowest prevalences (<10%) in the French centres and the 'health-conscious' group (UK). The prevalence of a large waist circumference or a high waist-to-hip ratio was high in centres from Spain, Greece, Ragusa and Naples (Italy) and among women from centres in Germany and Bilthoven (The Netherlands). Conclusions: Anthropometric measures varied considerably within the EPIC population. These data provide a strong base for further investigation of anthropometric measures in relation to the risk of chronic diseases, especially cancer.